Ultraviolet Photodetector Based on a Beta-Gallium Oxide/Nickel Oxide/Beta-Gallium Oxide Heterojunction Structure - Shinji Nakagomi (Sensors, 2023)
In this paper, an n–p–n structure based on a β-Ga2O3/NiO/β-Ga2O3 junction was fabricated. The device based on the β-Ga2O3/NiO/β-Ga2O3 structure, as an ultraviolet (UV) photodetector, was compared with a p–n diode based on a NiO/β-Ga2O3 structure, where it showed rectification and 10 times greater responsivity and amplified the photocurrent. The reverse current increased in proportion to the 1.5 power of UV light intensity. The photocurrent amplification was related to the accumulation of holes in the NiO layer given by the heterobarrier for holes from the NiO layer to the β-Ga2O3 layer. Moreover, the device could respond to an optical pulse of less than a few microseconds.